Adopsi Fintech dan Kinerja Keuangan UMKM: Tinjauan Konseptual tentang Pembayaran Digital, Pinjaman P2P, dan Manajemen Modal Kerja - Dyatri Utami Arina Absari (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
Digital financial transformation has reshaped how micro, small, and medium enterprises (MSMEs) manage payments, financing, cash flow, and working capital. This article examines the relationship between fintech adoption, digital payment, P2P lending, working capital management, and MSME financial performance through a qualitative library research approach using a Systematic Literature Review with Conceptual Framework Development. Data sources include scholarly articles from major academic databases and official documents from Bank Indonesia, the Financial Services Authority, Statistics Indonesia, and the Ministry of Cooperatives and SMEs. Literature selection follows PRISMA 2020 principles, while analysis applies thematic synthesis, content analysis, and framework synthesis. The conceptual findings indicate that digital payment may improve cash visibility and transaction traceability, while P2P lending may support working capital financing when used prudently. Working capital efficiency is positioned as the key mechanism linking fintech adoption and MSME financial performance. The article contributes an integrative framework for future empirical research agendas.